Emotional distress during the first year of the COVID-19 pandemic-large sample serbian study - Bojana Dunjic-Kostic; Marija Mitkovic-Voncina; Jelena Jovic; Emilija Eric; Marta Gostiljac; Stefan Jerotic; Nikola Lalovic; Milan Latas; Maja Pantovic-Stefanovic (Scientific Reports)
Abstract The COVID-19 pandemic has significantly impacted mental health, with healthcare professionals being particularly vulnerable. This study explores the emotional distress experienced in Serbia, focusing on factors that contribute to symptoms of depression, anxiety, and stress. A total of 3328 participants from the general and healthcare populations were surveyed using the Depression Anxiety Stress Scales—Short Form (DASS-21). The analysis revealed that certain groups, such as women, non-psychiatrist doctors, individuals with a history of mental disorders, and those dissatisfied with their financial, familial, and living circumstances, were more likely to experience heightened levels of emotional stress. Moreover, healthcare professionals, especially those working in challenging conditions, may be at increased risk for mental health issues. These findings underscore the need for targeted interventions and ongoing support for those most affected, particularly within the healthcare sector, to mitigate the long-term mental health impacts of the pandemic.